Sepiapterin Improves Vascular Reactivity and Insulin-Stimulated Glucose in Wistar Rats. (23rd September 2018) - Keller, A. C.; Knaub, L. A.; Scalzo, R. L.; Hull, S. E.; Johnston, A. E.; Walker, L. A.; Reusch, J. E. B.
Abstract : In the vasculature, sedentary behavior leads to endothelial abnormalities, resulting in elevated cardiovascular disease risk. Endothelial nitric oxide synthase (eNOS) aberrations characterize endothelial dysfunction; eNOS also regulates mitochondrial function. We hypothesized that sepiapterin (a precursor to eNOS cofactor tetrahydrobiopterin (BH4 )) supplementation would improve endothelium-dependent vascular relaxation in sedentary animals via modulation of NOS function and mitochondrial activity. Sedentary male Wistar rats were fed ad libitum for a total of 10 weeks. Sepiapterin was administered in diet during the final 5 weeks. Intraperitoneal insulin and glucose tolerance tests (IP-ITT/IP-GTT) were conducted at baseline and endpoint. Aorta was assessed for vasoreactivity and mitochondrial respiration. Insulin tolerance, determined by IP-ITT, significantly improved in rats treated with sepiapterin (p < 0.05, interaction of time and treatment). Acetylcholine- (ACh-) driven vasodilation was significantly greater in aorta from sepiapterin-treated rats as compared with control (76.4% versus 54.9% of phenylephrine contraction at 20 μ M ACh, p < 0.05 ). Sepiapterin treatment resulted in significantly elevated state 3 (9.00 oxygen pmol/sec ∗ mg versus 8.17 oxygen pmol/sec ∗ mg, p < 0.05 ) and 4 (7.28 oxygen pmol/sec ∗ mg versus 5.86 oxygen pmol/sec ∗ mg, p < 0.05 ) aortic mitochondrial respiration with significantly lower respiratory control ratio (p < 0.05 ) during octanoylcarnitine-driven respiration. Vasodilation and insulin sensitivity were improved through targeting NOS via sepiapterin supplementation.